The Phenomenon of Jilboobs Clothing on Social Media TikTok in PTR Account @OKLINFIA: Fenomena Pakaian Jilboobs di Media Sosial TikTok dalam Akun PTR @OKLINFIA - Farah Hafhida; Nur Maghfirah Aesthetika (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the persisting Jilboobs phenomenon within social and cyberspace, specifically focusing on its manifestation through the TikTok account @Oklinfia. Grounded in qualitative research, data was collected through netnography, utilizing Culture, Online/Digital Traces, Participants/Interactions, and Immersive Engagement as analytical dimensions. The findings reveal that while Jilboobs has become an annual cultural occurrence, @Oklinfia's PTR content imbues this phenomenon with a visual significance leaning towards a sexualized narrative. This intentional direction aims to capture male attention, resulting in increased views and virality on the TikTok platform. The implications of these findings shed light on the evolving nature of cultural trends within digital spaces and the potential impact on societal perceptions of modesty and religious adherence. Highlights : Cultural Evolution: Examining the annual recurrence of the Jilboobs phenomenon highlights its cultural persistence in social and digital spheres. Visual Significance: @Oklinfia's PTR content demonstrates a deliberate visual orientation, incorporating sexualized elements to capture and sustain male attention on TikTok. Netnographic Insight: Utilizing netnography with a focus on Culture, Online/Digital Traces, Participants/Interactions, and Immersive Engagement provides valuable insights into the evolving landscape of digital cultural trends. Keywords: Jilboobs Phenomenon, TikTok, Netnography, Visual Culture, Social Media Trends